3D bioprinting: Materials, processes, and applications. Issue 2 (2022) - Bartolo, Paulo; Malshe, Ajay; Ferraris, Eleonora; Koc, Bahattin
Abstract: Ageing population and new diseases are requiring the development of novel therapeutical strategies. 3D bioprinting an novel application domain of additive manufacturing emerged as a potential transformative strategy for tissue engineering and regenerative medicine. This paper introduces the concept of 3D bioprinting, discussing in detail key requirements of bio-inks and main materials used to encapsulate cells. Recent advances related to the use of smart materials and the concept of 4D printing is also discussed. Main 3D bioprinting techniques are described in detail and key limitations highlighted. Successful cases, demonstrating the relevance of 3D bioprinting are also presented. Finally, the paper addresses the main research challenges and future perspectives in the field of 3D bioprinting.